2009
DOI: 10.1007/s00192-009-0808-y
|View full text |Cite
|
Sign up to set email alerts
|

Incontinence quality of life questionnaire (I-QOL): translation and validation study of the Iranian version

Abstract: The Persian version of the I-QOL can be used for measuring QOL in urinary incontinent women in Iran.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 13 publications
3
14
3
Order By: Relevance
“…The result of the present study illustrates that, more than half of the study sample had duration of urinary incontinence about 1 to less than 3 years. This result disagrees with a study carried out by [29] his result showed that less than half of the study sample had length of time with urinary incontinence about one year.…”
Section: From View Point Of Researcher Theses Differences In Results contrasting
confidence: 98%
See 2 more Smart Citations
“…The result of the present study illustrates that, more than half of the study sample had duration of urinary incontinence about 1 to less than 3 years. This result disagrees with a study carried out by [29] his result showed that less than half of the study sample had length of time with urinary incontinence about one year.…”
Section: From View Point Of Researcher Theses Differences In Results contrasting
confidence: 98%
“…Also about two thirds of the study sample had frequency urinary incontinence (day) 3-4 times. This result disagreement with a study carried out by [29] his result showed that less than one third of sample had urinary incontinence (last month) about 2-3 occurrences (per week), on other hand about one third of the sample had frequency urinary incontinence (day) 1-2 occurrences (per day) respectively. From view point of researcher this may explain the reasons of seeking professional help and attending the gynaecological units.…”
Section: From View Point Of Researcher Theses Differences In Results contrasting
confidence: 97%
See 1 more Smart Citation
“…Stress UI was the most common type of incontinence followed by mixed UI and urge UI among women reporting UI in the current study. SUI has been reported as the most common UI type in women in many studies conducted . The result regarding UI types in our study was similar to those the literature.…”
Section: Discussionsupporting
confidence: 91%
“…Each item can be rated on a ve-point scale where 1 = extremely, 2 = quite a bit, 3 = moderately, 4 = a little, and 5 = not at all. The total I-QOL score and three domain scores are calculated by summing the unweighted item scores and transforming them into a 100-point scale where 0 = no problem, and 100 = most severe (Nojomi et al, 2009).…”
Section: Methodsmentioning
confidence: 99%